2019
DOI: 10.1177/1534735419866919
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion as a Therapy for Breast Cancer–Related Lymphedema in Female Adults: A Preliminary Randomized Controlled Trial

Abstract: Objective: To evaluate the effect of moxibustion on relieving breast cancer–related lymphedema. Materials and Methods: A randomized controlled trial was conducted in our institution from March 2016 to March 2017. All patients (N = 48) with cancer-related lymphedema were allocated to 2 groups: a treatment group, in which moxibustion was performed, and a control group, in which pneumatic circulation was performed with compression garments worn every day. Therapeutic efficacy was evaluated by measuring arm circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 25 publications
(40 reference statements)
0
42
0
Order By: Relevance
“…The number of TCM visits from cancer patients increased from 43.8 to 85.2%, compared with that in the same months last year. Clinical studies have found that TCM participation in cancer treatment can improve the quality of life and reinforce the effects of chemotherapy and radiotherapy [ 8 , 9 ]. In addition, TCM treatment can increase the survival time of cancer patients and reduce overall medical costs [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of TCM visits from cancer patients increased from 43.8 to 85.2%, compared with that in the same months last year. Clinical studies have found that TCM participation in cancer treatment can improve the quality of life and reinforce the effects of chemotherapy and radiotherapy [ 8 , 9 ]. In addition, TCM treatment can increase the survival time of cancer patients and reduce overall medical costs [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 In recent years, moxibustion has been applied in the treatment of several diseases, such as temporomandibular joint disturbance syndrome, malposition, colitis, dysmenorrhea, herpes zoster, knee osteoarthritis, diarrhea, heel pain, asthma, soft tissue injury, urinary retention, and gastrointestinal disorders. [7][8][9] More importantly, moxibustion has been used to improve the quality of life and alleviate the adverse effects of conventional treatment options for various diseases. 10 The incidence of breast cancer has rapidly increased worldwide, with a total incidence rising nearly 10 times in just 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of a conventional moxibustion study also mentioned that subjective symptoms improved although there was no measurable reduction in circumference. 15 As EORTC QLQ-BR23 is the first disease-specific questionnaire and it is the most widely used questionnaire, it may not be appropriate for patients with mild symptoms like our study. In future study, inclusion of additional outcome measures that may effectively reflect such symptoms should be considered.…”
Section: Discussionmentioning
confidence: 86%
“…26 However, to date, only a preliminary study has explored the effects of moxibustion for treating BCRL. 15 …”
Section: Introductionmentioning
confidence: 99%